Optimization of the quadratic assignment problem using an ant colony algorithm - Demirel, Nihan Cetin; Toksari, M. Duran (ELSEVIER SCIENCE INC, 2006)
Ant algorithm is a multi-agent systems inspired by the behaviors of real ant colonies function to solve optimization problems. In this paper an ant colony optimization algorithm is developed to solve the quadratic assignment problem. The local search process of the algorithm is simulated annealing. In the exploration of the search space, the evaluation of pheromones which are laid on the ground by ants is used. In this work, the algorithm is analyzed by using current problems in the literature and is compared with other metaheuristics. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: ant colony optimization; simulated annealing; metaheuristics; quadratic assignment problem; combinatorial optimization; Mathematics